Active Directory Bible - Simmons, Curt (Wiley Publishing, 2011)
With the release of Windows 2000, Microsoft introduced an entirely new approach to networking involving directory services. IT professionals are now responsible for designing a Windows 2000 Active Directory infrastructure, implementing it, maintaining it, and using Windows 2000 support technologies. This comprehensive Bible gives you all the knowledge necessary to successfully plan, deploy, and maintain an Active Directory network.